Wicked Jack - Wooldridge, Connie Nordhielm; Hillenbrand, Will (New York : Holiday House, 1995)
A mean old blacksmith's actions leave him unwelcomed by both Saint Peter and the Devil when he dies.
Keywords: Folklore -- United States